2018
DOI: 10.1002/vms3.121
|View full text |Cite
|
Sign up to set email alerts
|

Follicular development of canine ovaries stimulated by a combination treatment of eCG and hCG

Abstract: Ovarian follicular dynamics is not well known in dogs. Imaging of ovaries is technically difficult; however, ovaries clamped at a subcutaneous site can more easily be monitored using ultrasound imaging. This study investigated the follicular development of canine ovaries stimulated by hormone treatment using ultrasound imaging of the ovaries clamped at a subcutaneous site. Oestrus was induced using subcutaneous administration of 500 IU equine chorionic gonadotropin (eCG) and 1000 IU human chorionic gonadotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this study, the date of ovulation was identified in 93.6% of the initially confirmed follicles. The use of high‐frequency (18 MHz) probe is thought to have contributed to the improved accuracy in this study, whereas 7.5–13 MHz probe was used in previous studies (Renton et al., 1992; Boyd et al., 1993; England &Yeager, 1993; Hayer et al., 1993; Hase et al., 2000; Fontbonne & Malandian, 2006; Bergeron et al., 2013; Domosławska et al., 2014; Hirata et al., 2018). Another factor the accuracy depends on is the operator's experience.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, the date of ovulation was identified in 93.6% of the initially confirmed follicles. The use of high‐frequency (18 MHz) probe is thought to have contributed to the improved accuracy in this study, whereas 7.5–13 MHz probe was used in previous studies (Renton et al., 1992; Boyd et al., 1993; England &Yeager, 1993; Hayer et al., 1993; Hase et al., 2000; Fontbonne & Malandian, 2006; Bergeron et al., 2013; Domosławska et al., 2014; Hirata et al., 2018). Another factor the accuracy depends on is the operator's experience.…”
Section: Discussionmentioning
confidence: 87%
“…England and Yeager (1993) suggested that detection of ovulation with ultrasound has limited practical value. Since no method has been established to accurately determine or predict ovulation, ovaries have been surgically clamped at a subcutaneous site for ultrasound imaging to evaluate follicular development (Hirata et al., 2018). It has been reported that pre‐ovulatory follicles in many cases are located very close to each other (Fontbonne & Malandian, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral malacotomy of four queens was performed using a ventral‐flank abdominal approach using routine techniques and materials, according to the methods described by Hirata et al (2018). Briefly, the queen was mechanically ventilated with isoflurane in pure oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, ultrasound echogenicity of corpora lutea is variable and depends on the observation period, thus making sonographic detection difficult (Gatel et al., 2020). However, when ovaries are clamped at a subcutaneous site, their follicular growth can more easily be monitored using ultrasound imaging (Hirata et al., 2018). Moreover, the ovarian clamp at the subcutaneous site can provide easy access for repeated collection of oocytes for in vitro fertilization in endangered animals.…”
Section: Introductionmentioning
confidence: 99%